Hyperlexia in spanish-speaking children: report of 2 cases from Colombia, South America (2006)
Hyperlexia is a condition rarely reported in Spanish-speaking children, characterized by the ability to recognize written words without formal training. We present two unrelated autistic children with hyperlexia from Colombia (South America) who were followed for 8 years with formal neuropsychological evaluations of language, motor skills, visual perception, attention and behavior. Both children taught themselves to read before 5 years of age but showed minimal comprehension; both displayed obsessional reading and difficulties in social skills and attention. Brain CT scans were normal. Hyperlexia has been associated with hyperactivation of the left superior temporal cortex; we conclude that the orthographic route is a probable mechanism for the development of hyperlexia.